BISNIS KALIGRAFI DALAM TINJAUAN EKONOMI ISLAM - Mulyadi Mulyadi; As Sauti Wahid (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy is part of Islamic art. Its appearance coincided with the spread of Islam in the ignorant Arab society until it spread to various parts of the world. Art that emerged as a result of Islamic civilization basically has a high meaning and value. Calligraphy is a work that has meaning because the work is an expression of divinity which is abstract in nature. Thus, calligraphy contains a communication between the artist and the Creator which is interpreted through expressions in painting or writing calligraphy from revelation (the Koran). In completing this study, researchers used the method of literature study. Literature study is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. In running this business, calligraphy craftsmen are also oriented not only to seek worldly benefits but also to seek the pleasure of Allah SWT, calligraphy craftsmen have carried out several principles of Islamic economics, including the principles of divinity, justice, responsibility, and truth